AB0890 Is There a Relationship Between Vitamin D and Schizophrenia?. (9th June 2015) - Grados, D.; Salavert, J.; Ramiro, N.; Carriόn, M.; Ramírez, N.; Erra, A.
Abstract : Background: Studies suggest a neuroprotective role for vitamin D. Its deficit has been linked with various psychiatric disorders such as schizophrenia (1). Increase in the prevalence of schizophrenia has been associated with high latitudes, winter/spring births, migration, urbanicity and cold climates (2, 3). Vitamin D deficiency could be an important environmental risk factor, linking all of the previously exposed. Objectives: We aimed to determine whether patients with a first psychotic episode had low levels of vitamin D compared to controls, considering their final diagnoses (schizophrenia vs other psychoses). Methods: Cross-sectional study in an acute inpatient psychiatric unit. Vitamin D (25-hydroxyvitamin D) was determined by direct competitive chemiluminescence immunoassay. Vitamin D levels (ng/ml) were considered optimum >30, insufficient 20–30 and deficient <20 (4). Final diagnosis was obtained from the outpatient mental health service after a 6 month follow-up. Results: We analyzed 27 patients with first-episode psychosis (13 with final diagnosis of schizophrenia and 14 of other psychoses) and 17 healthy controls, with no differences in mean age between the three groups (χ 2 (2)=5.20, p>0.05). Schizophrenic patients showed deficient average values (ng/ml) of vitamin D (mean 12.87, range 6-24.9). Vitamin D levels in the other psychoses patient group were higher but also deficient (mean 15.74, range 6-34.6). Controls presented higher levels of vitamin D, but still insufficient (mean 21.45, range 11.20-33.5). Vitamin D levels in the schizophrenia group were significantly lower compared to controls (CI 1.8 – 15.4; p<0.009). No other significant differences were found between groups. Conclusions: We observed deficient vitamin D levels in all the patients studied, being significantly lower for schizophrenic patients. Future studies are required to further examine this association in schizophrenia because vitamin D deficiency may be an easily modifiable risk factor by means of a cheap and save public health intervention. References: Belvederi Murri, M., Respino, M., et al. 2013 Vitamin D and psychosis: mini meta-analysis. Schizophr Res 150, 235-239. McGrath, J. J., Eyles, D.W., et al. 2010 Neonatal vitamin D status and risk of schizophrenia: a populationbased case-control study. Arch Gen Psychiatry 67, 889-94. McGrath, J. J., Burne, T.H., et al. 2010 Developmental vitamin D deficiency and risk of schizophrenia: a 10-year update. Schizophr Bull 36, 1073-8. Holick, M.F. 2007 Vitamin D deficiency. N Engl J Med 357, 266-81. Disclosure of Interest: None declared